Meat and Meat Mutagens and Risk of Prostate Cancer in the Agricultural Health Study - Koutros, Stella (2008)
Meats cooked at high temperatures, such as pan-frying or grilling, are a source of carcinogenic heterocyclic amines and polycyclic aromatic hydrocarbons. We prospectively examined the association between meat types, meat cooking methods, meat doneness, and meat mutagens and the risk for prostate cancer in the Agricultural Health Study. We estimated relative risks (RR) and 95% confidence intervals (CI) for prostate cancer using Cox proportional hazards regression, using age as the underlying time metric and adjusting for state of residence, race, smoking status, and family history of prostate cancer. During 197,017 person years of follow-up, we observed 668 incident prostate cancer cases (613 of these were diagnosed after the first year of follow-up and 140 were advanced cases) among 23,080 men with complete dietary data. We found no association between meat type or specific cooking method and prostate cancer risk. However, intake of well or very well done total meat was associated with a 1.26-fold increased risk of incident prostate cancer (95% CI 1.02, 1.54) and a 1.97-fold increased risk (95% CI 1.26, 3.08) of advanced disease when the highest tertile was compared with the lowest. Risks for the two heterocyclic amines 2-amino-3,4,8-trimethylimidazo-[4,5-f]quinoxaline (DiMeIQx) and 2-amino-3,8-dimethylimidazo-[4,5-b]quinoxaline (MeIQx) were of borderline significance for incident disease, 1.24 (95% CI 0.96, 1.59) and 1.20 (95% CI 0.93, 1.55) respectively, when the highest quintile was compared with the lowest. In conclusion, well and very well done meat was associated with an increased risk for prostate cancer in this cohort.